Guidelines for Research Proposal Writing in the Social Sciences - Bhattachan, Krishna Bahadur (Himalayan Journal of Sociology and Anthropology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> No abstract available Himalayan Journal of Sociology & Anthropology Vol.1 2004 p.99-105